(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
When choosing the size, shape and material of gabions, it is determined depending on the area of the place to be improved. Gabions can be used not only for design, but also for protection against erosion. Gabions not only decorate the suburban area, but also protect riverbeds from erosion, strengthen slopes, and prevent soil erosion.